2016
DOI: 10.1128/aem.01575-16
|View full text |Cite
|
Sign up to set email alerts
|

Variable High-Pressure-Processing Sensitivities for Genogroup II Human Noroviruses

Abstract: Human norovirus (HuNoV) is a leading cause of foodborne diseases worldwide. High-pressure processing (HPP) is one of the most promising nonthermal technologies for the decontamination of viral pathogens in foods. However, the survival of HuNoVs after HPP is poorly understood because these viruses cannot be propagated in vitro. In this study, we estimated the survival of different HuNoV strains within genogroup II (GII) after HPP treatment using viral receptor-binding ability as an indicator. Four HuNoV strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The dependency on the surrounding matrix of the response of bacterial cells to HPP treatment is a well-established phenomenon, with salt concentration, pH, fat content, and the presence of specific molecules reported to affect cell survival the variables (49). Similar observations have been made for viruses, with pH, temperature and solute concentration reported as variables in the response of norovirus to HPP (45). The presence of food components has been demonstrated to protect viral capsids from HPP denaturation (50).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The dependency on the surrounding matrix of the response of bacterial cells to HPP treatment is a well-established phenomenon, with salt concentration, pH, fat content, and the presence of specific molecules reported to affect cell survival the variables (49). Similar observations have been made for viruses, with pH, temperature and solute concentration reported as variables in the response of norovirus to HPP (45). The presence of food components has been demonstrated to protect viral capsids from HPP denaturation (50).…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, in feline calicivirus (FCV) (a surrogate for norovirus) 3 log reductions were observed at 200 MPa and no infectious particles were recovered following treatment at 275 MPa (44). Inactivation of norovirus suspended in buffer has been reported at pressures in excess of 200 MPa (5 min hold, 4 °C), but the sensitivity to pressure was variable between the four strains studied, with the most sensitive strain reduced by 4 log at 600 MPa and the least sensitive by only 1 log under the same conditions (45).…”
Section: Discussionmentioning
confidence: 99%
“…The dependency on the surrounding matrix of the response of bacterial cells to HPP treatment is a well-established phenomenon, with salt concentration, pH, fat content, and the presence of specific molecules reported to affect cell survival (Balamurugan et al, 2018). Similar observations have been made for viruses, with pH, temperature, and solute concentration reported as variables in the response of norovirus to HPP (Lou et al, 2016). The presence of food components has been demonstrated to protect viral capsids from HPP denaturation (Komora et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, for feline calicivirus (FCV) (a surrogate for norovirus) 3 log reductions were observed at 200 MPa and no infectious particles were recovered following treatment at 275 MPa (Kingsley et al, 2002). Inactivation of norovirus suspended in buffer has been reported at pressures in excess of 200 MPa (5 min hold, 4 • C), but the sensitivity to pressure was variable between the four strains studied, with the most sensitive strain reduced by 4 log at 600 MPa and the least sensitive by only 1 log under the same conditions (Lou et al, 2016). Therefore, it can be concluded that the inactivation efficiency of HPP depends on the studied virus and its surrounding matrix.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation